Thioether-Based Fluorescent Covalent Organic Framework for Selective Detection and Facile Removal of Mercury(II) - Ding, San-Yuan; Dong, Ming; Wang, Ya-Wen; Chen, Yan-Tao; Wang, Huai-Zhen; Su, Cheng-Yong; Wang, Wei (Journal of the American Chemical Society, 2016)
Heavy metal ions are highly toxic and widely spread as environmental pollutants. New strategies are being developed to simultaneously detect and remove these toxic ions. Herein, we take the intrinsic advantage of covalent organic frameworks (COFs) and develop fluorescent COFs for sensing applications. As a proof-of-concept, a thioether-functionalized COF material, COF-LZU8, was “bottom-up” integrated with multifunctionality for the selective detection and facile removal of mercury(II): the π-conjugated framework as the signal transducer, the evenly and densely distributed thioether groups as the Hg2+ receptor, the regular pores facilitating the real-time detection and mass transfer, together with the robust COF structure for recycle use. The excellent sensing performance of COF-LZU8 was achieved in terms of high sensitivity, excellent selectivity, easy visibility, and real-time response. Meanwhile, the efficient removal of Hg2+ from water and the recycling of COF-LZU8 offers the possibility for practical applications. In addition, X-ray photoelectron spectroscopy and solid-state NMR investigations verified the strong and selective interaction between Hg2+ and the thioether groups of COF-LZU8. This research not only demonstrates the utilization of fluorescent COFs for both sensing and removal of metal ions but also highlights the facile construction of functionalized COFs for environmental applications.